Australia and Creation of Democratic Republic of East Timor - E V Esakova (Vestnik RUDN International Relations, 2011)
The article considers the prerequisites and stages of creating a new independent state - democratic republic of East Timor. On focus are the role of Australia, neighboring states as well as the role of UN and international community in this process.